Semarang College Students’ Views on Beauty Standards & Diversity in Indonesian Skincare & Bodycare Advertisements - Priskila, Cristyvilda; Ningtyas, Sulistya (Sabda: Jurnal Kajian Kebudayaan, 2021)
Beauty standards that spread widely in society make people treat some different from the other. It also influence how people see a person in a formal context, like in recruiting job or school. Unfortunately, this perennial bias also appear in how Indonesian skincare and body care brands make their advertisements. The advertisements usually only show model with particular beauty standards and left diversity behind, forgetting that beauty cannot be defined as simple as that. This research take a depth look about it through the interviews with selected Semarang college students. The research explores about those advertisements and its impact of how people define beauty. Aiming to understand college students’ point of view of mentioned issue, this research wants to become a starting step in changing the prevailing beauty standards.